Profile of 25-Hydroxyvitamin D in Individuals Attending Armed Forces Institute of Pathology (AFIP), Dhaka - Parvin, Mimi; Sarkar, Mreenal Kanti; Saha, Debashis (Journal of Enam Medical College, 2018)
Background: In the last two decades, there has been increasing interest in the biology of vitamin D and a growing recognition is that vitamin D deficiency is common in tropical countries despite having ample sunshine. Myth of ‘routine exposure to sunshine does not require extra vitamin D’ results in severe asymptomatic vitamin D deficiency. Several factors like socio-economic condition, dietary insufficiency, inadequate exposure to sunlight due to use of sun-screen, clothes, environmental pollution, skin pigmentation may contribute to vitamin D deficiency. Objective: The study was designed to evaluate the vitamin D status of patients of different age groups reporting to Armed Forces Institute of Pathology (AFIP), Dhaka. Materials and Methods: This crosssectional, observational study was conducted from October 2015 to March 2017, using serum 25-hydroxyvitamin D (25-OHD) levels to classify patients of different age groups into deficient, insufficient and sufficient categories. Individuals up to 70 years of age of all religions, genders and occupations who gave blood specimens at AFIP were included in the study. Patients with chronic renal failure, primary hyperparathyroidism, on vitamin D supplementation with established diagnosis of osteomalacia and rickets, taking phenytoin or glucocorticoids were excluded. Total 25-OH vitamin D level in serum was estimated by electro-chemiluminescence on Cobas Elecsys e411 fully automated system on the day of collection. This method has been standardized against LC-MS/MS which in turn has been standardized to the NIST (National Institute of Standards and Technology, USA). The functional sensitivity was determined to be 4.01 ng/mL (CV 18.5%). Vitamin D deficiency is defined as 25(OH) D <50 nmol/L, insufficiency as 50–75 nmol/L and sufficiency as ≥75 nmol/L and toxicity >375 nmol/L. The definition of vitamin D status was based on the recommendation of the US Institute of Medicine (IOM) for vitamin D. Results: A total of 2867 specimens were enrolled in the study, comprising 1949 (67.98%) female and 918 (32.02%) male. Maximum number (1270) was in the age range of 41−60 years. According to vitamin D status 1640 (57.20%) out of 2867 were found deficient, among which female were 1175 (71.65%) and male 465 (28.35%) with 1:2.5 male and female ratio. There were 255 male (37.83%) and 419 (62.17%) female in the insufficient group with 1:1.64 male-female ratio. Lowest value of <7.5 nmol/L was found in 36 subjects where 80.55% were female. Female were also found to be predominant (62.75%) in highest concentration of vitamin D (>175 nmol/L). Female in all age groups predominated in both deficiency and insufficiency groups. No toxic values were found in any age group among male or female. Conclusion: Vitamin D deficiency is pandemic; it has been assumed that one billion people worldwide have vitamin D deficiency or insufficiency. Laboratory professionals are confronted with substantial increase in laboratory testing due to growing clinical interest in vitamin D status. At the same time avoidance of overscreening of vitamin D by physicians should also be considered. J Enam Med Col 2018; 8(1): 35-40